Hybrid layer-by-layer composites based on a conducting polyelectrolyte and Fe3O4 nanostructures grafted onto graphene for supercapacitor application. Issue 45 (15th October 2015) - Pardieu, Elodie; Pronkin, Sergey; Dolci, Mathias; Dintzer, Thierry; Pichon, Benoit P.; Begin, Dominique; Pham-Huu, Cuong; Schaaf, Pierre; Begin-Colin, Sylvie; Boulmedais, Fouzia
Abstract : Iron oxide raspberry grafted onto graphene/PEDOT:PSS layer-by-layer has been designed for supercapacitors. Abstract : Using the layer-by-layer process, we developed a new and original ternary hybrid material based on magnetite iron oxide raspberry nanostructures, 250–300 nm in size, synthesized directly on few layer graphene (Fe3 O4 @FLG) alternated with conducting poly(3, 4-ethylenedioxy thiophene):poly(styrene sulfonate) (PEDOT:PSS) as the electrode material for supercapacitors. Magnetite based nanostructures were used as electroactive materials. Graphene and PEDOT:PSS ensured the electrical conductivity. PEDOT:PSS also plays the role of a binder conferring cohesion to the hybrid material. Using spin-coating, the step-by-step buildup leads to very regular and well controlled film properties such as the film thickness and the content of iron oxide. The electrochemical properties of the so-obtained hybrid material were investigated in 0.5 M Na2 SO3 aqueous electrolyte by cyclic voltammetry, electrochemical impedance spectroscopy and chronopotentiometry. In contradiction with the reported poor capacitance and poor cycling stability of iron oxide based supercapacitors, hybrid Fe3 O4 @FLG/PEDOT:PSS multilayers provide a high specific capacitance (153 F g −1 at 0.1 A g −1 ) and a high structural and cycling stability (114% retention after 3500 cycles). This hybrid developed system opens the route for even higher specific capacitance using other types of metal oxides.